The Effects of Formative Assessment on Student Motivation : Perspectives of Primary School Teachers, Students and Parents in Azerbaijan - Hummatova, Lala (ADA University, 2022)
Formative assessment, which is also called assessment for learning, is an integral part of learning, and its role in children’s learning motivation is undeniable. This qualitative research aimed to explore the relationship between formative assessment and primary school children’s learning motivation in Azerbaijan, as well as primary school teachers', students', and parents' perceptions about the application of formative assessment. The research was conducted in two primary schools of Azerbaijan. The instruments for the study were semi-structured interviews, classroom observation, and document analysis. Seven primary school teachers and eight primary school children were interviewed face-to-face to explore their perceptions of formative assessment. Besides, focus group interviews with three parents and as well as face-to-face interviews with two parents, were conducted to receive more data for this study. Additionally, classroom observation and document analysis of the students’ diaries, classroom journals and teachers’ formative journals aimed to determine teachers’ formative assessment practices within the classroom. The major findings of the study showed that the interviewed participants highlighted the value and significance of feedback received as a formative assessment technique by teachers. However, there were some misperceptions toward formative assessment practices within the classroom among the interviewed participants as many of the participants were equating the word “grade” and “feedback” during the interview process. Also, the findings revealed that parents and children have difficulties in understanding written feedback as a formative assessment technique. Since the findings of this study revealed that there is a relationship between formative assessment and primary school children’s learning motivation, it can be mentioned that formative assessment can serve as a learning aid, enhancing the learning process and outcomes of learning. Thus, this study suggests doing research on the correlation between formative assessment and students’ learning motivation with other age groups as this study only focused on primary school children.
Keywords: Formative assessment.; Feedback system.; Schools, Primary -- Formative assessment.; Education